Eco Soma Pain and Joy in Speculative Performance Encounters - Kuppers, Petra (Art After Nature, 2022)
Modeling a disability culture perspective on performance practice toward socially just futures In Eco Soma, Petra Kuppers asks readers to be alert to their own embodied responses to art practice and to pay attention to themselves as active participants in a shared sociocultural world. Reading contemporary performance encounters and artful engagements, this book models a disability culture sensitivity to living in a shared world, oriented toward more socially just futures. Eco soma methods mix and merge realities on the edges of lived experience and site-specific performance. Kuppers invites us to become moths, sprout gills, listen to our heart's drum, and take starships into crip time. And fantasy is central to these engagements: feeling/sensing monsters, catastrophes, golden lines, heartbeats, injured sharks, dotted salamanders, kissing mammoths, and more. Kuppers illuminates ecopoetic disability culture perspectives, contending that disabled people and their co-conspirators make art to live in a changing world, in contact with feminist, queer, trans, racialized, and Indigenous art projects. By offering new ways to think, frame, and feel "environments," Kuppers focuses on art-based methods of envisioning change and argues that disability can offer imaginative ways toward living well and with agency in change, unrest, and challenge. Traditional somatics teach us how to fine-tune our introspective senses and to open up the world of our own bodies, while eco soma methods extend that attention toward the creative possibilities of the reach between self, others, and the land. Eco Soma proposes an art/life method of sensory tuning to the inside and the outside simultaneously, a method that allows for a wider opening toward ethical cohabitation with human and more-than-human others.